In Vivo Behavior of the Tandem Glycine Riboswitch in Bacillus subtilis - Arianne M. Babina (American Society for Microbiology, 2017)
ABSTRACT In many bacterial species, the glycine riboswitch is composed of two homologous ligand-binding domains (aptamers) that each bind glycine and act together to regulate the expression of glycine metabolic and transport genes. While the structure and molecular dynamics of the tandem glycine riboswitch have been the subject of numerous in vitro studies, the in vivo behavior of the riboswitch remains largely uncharacterized. To examine the proposed models of tandem glycine riboswitch function in a biologically relevant context, we characterized the regulatory activity of mutations to the riboswitch structure in Bacillus subtilis using β-galactosidase assays. To assess the impact disruptions to riboswitch function have on cell fitness, we introduced these mutations into the native locus of the tandem glycine riboswitch within the B. subtilis genome. Our results indicate that glycine does not need to bind both aptamers for regulation in vivo and mutations perturbing riboswitch tertiary structure have the most severe effect on riboswitch function and gene expression. We also find that in B. subtilis, the glycine riboswitch-regulated gcvT operon is important for glycine detoxification. IMPORTANCE The glycine riboswitch is a unique cis-acting mRNA element that contains two tandem homologous glycine-binding domains that act on a single expression platform to regulate gene expression in response to glycine. While many in vitro experiments have characterized the tandem architecture of the glycine riboswitch, little work has investigated the behavior of this riboswitch in vivo. In this study, we analyzed the proposed models of tandem glycine riboswitch regulation in the context of its native locus within the Bacillus subtilis genome and examined how disruptions to glycine riboswitch function impact organismal fitness. Our work offers new insights into riboswitch function in vivo and reinforces the potential of riboswitches as novel antimicrobial targets.